2013
DOI: 10.7598/cst2013.387
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition Effect of Corrosion of Carbon Steel in Seawater by Diethylene Triamine Pentamethylene Phosphonic Acid and Al3+ System

Abstract: The inhibition of the corrosion of carbon steel in seawater by diethylene triamine pentamethylene phosphonic acid (DTPMP) and Al 3+ has been investigated using weight loss and electrochemical measurements. The results show that 65% inhibition efficiency is achieved with binary system consisting of 250 ppm of DTPMP and 50 ppm of Al 3+. Polarization curves indicate that the system is a mixed inhibitor. The surface morphology of the metal surface is examined using the scanning electron microscope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…Polarization study has been used to detect the formation of a protective film on the metal surface [27][28][29][30][31][32]. When a protective film is formed on the metal surface, the linear polarization resistance (LPR) increases and the corrosion current (I corr ) decreases.…”
Section: Potentiodynamic Polarization Studymentioning
confidence: 99%
“…Polarization study has been used to detect the formation of a protective film on the metal surface [27][28][29][30][31][32]. When a protective film is formed on the metal surface, the linear polarization resistance (LPR) increases and the corrosion current (I corr ) decreases.…”
Section: Potentiodynamic Polarization Studymentioning
confidence: 99%
“…is identified by the X‐ray single‐crystal analysis . In contrast to known zinc‐phosphonate inhibitors, it contains the Zn–N bond in the coordination environment of zinc. A nitrogen atom is deprotonated, and it participates in the formation of the donor–acceptor bond with a zinc atom coordinated in the configuration of a distorted trigonal bipyramid.…”
Section: Resultsmentioning
confidence: 99%
“…The use of the coordination complexes of zinc with organophosphonic acids as corrosion inhibitors was offered long ago; however, the mechanism of their protective effect has not been unambiguously identified yet. The studies of a number of researchers have shown that in different cases, either the preferential influence of precipitation of the zinc coordination hydroxides on the cathode reaction kinetics or the influence of the surface complexation on kinetics of the anode metal ions transfer is possible.…”
Section: Introductionmentioning
confidence: 99%
“…The corrosion resistance of aluminum alloy in aggressive environment is not good, as the natural oxide film on aluminum alloy cannot offer sufficient protection against aggressive anions. Therefore, there are several effective anti‐corrosion inhibitors like nitrate, phosphate, phosphonic acids , and other organic molecules , used in dissolved form that can control the metal dissolution either in acidic, in alkaline or in neutral solutions. The presence of chloride ion is a special case as the aluminum is very sensitive for pitting corrosion .…”
Section: Introductionmentioning
confidence: 99%
“…Controversially, the carboxylic, phosphonic, and sulfonic acids form SAM layers only on oxide film of metals. Phosphonic acid SAMs are increasingly used for building thin films due to their ability to form well defined and stable layers on oxide surfaces . As a native oxide film covers almost all engineered metals, the application of organic SAM coatings for corrosion protection is of high technological importance .…”
Section: Introductionmentioning
confidence: 99%